Nuzi Marginalia - Speiser, E. A.
1. The Human Equivalent of sikiltu(m) — 2. OB k/ḫiššatum: Nuzi ḫi/eššumaku — 3. The Hurrian Element -maku — 4. Ceremonial Payment — 5. The Terminology of the Oath by the Gods.